Investigating Children’s Narrative Abilities in a Chinese and Multilingual Context: Cantonese, Mandarin, Kam and Urdu Adaptations of the Multilingual Assessment Instrument for Narratives (MAIN) - Kan, Rachel T. Y.; Chan, Angel; Gagarina, Natalia (Frontiers in Psychology, 2020)
This article introduces the LITMUS MAIN (Language Impairment Testing in Multilingual Settings-MAIN) and motivates the adaptation of this instrument into Chinese languages and language pairs involving a Chinese language, namely Cantonese, Mandarin, Kam, Urdu. We propose that these new adapted protocols not only contribute to the theoretical discussion on story grammar and widen the evidential base of MAIN to include more languages in studying bilinguals, they also offer new methods of assessing language development in young children that can tease apart the effects of language impairment and bilingualism and improve the identification of Developmental Language Disorder. These new protocols are the first tools to be designed for the assessment of language skills, in general, and narrative skills, in particular, in bilingual children speaking these languages. By catering to under-researched languages and over-looked groups of bilingual children, these new tools can improve the clinical management for certain bilingual ethnic minority children such as Urdu-Cantonese and Kam-Mandarin bilinguals, as well as promote the study of these groups and their acquisition issues. Advances in understanding the theoretical and acquisition issues in childhood bilingualism can also be made possible using these new tools.